Nanofabrication and investigation of ground state degeneracy in artificial spin ice lattices - Oliveira, Lara Braga de (2024)
Arrays of geometrically frustrated nanomagnets known as artificial spin ices (ASIs) have been proposed as an intriguing system for investigating collective excitations that behave as emergent magnetic monopoles at room temperature. This was only made possible due to advances in lithography techniques, enabling the nanofabrication of two-dimensional lattices with potential use in devices. However, in general, in these artificial systems, emergent magnetic monopoles cannot move freely as in their natural counterpart because energy strings connecting monopoles of opposite charges arise. Furthermore, the energy of the string connecting them is strictly related to the non-degeneracy of the ground state. Therefore, several theoretical works have proposed that two-dimensional lattices with specific geometries could exhibit a highly degenerate ground state and, consequently, free monopoles in the lattice. Such specific geometries are rectangular arrays of disconnected nanomagnets, where the ratio between the horizontal and vertical distances between them is equal to square root of three; and connected square arrays of nanomagnets. In this context, the present work aimed to experimentally investigate the proposed degeneracy in such ASI geometries through characterization techniques such as magnetic force microscopy and magnetoresistance. Additionally, these systems are usually fabricated by nanofabrication processes involving expensive and time-consuming physical vapor deposition techniques. As a possible solution to this problem, we present a new nanofabrication route using the electrodeposition technique for the growth of Permalloy, offering an alternative to manufacture ASIs quickly and affordably. Keywords: artificial spin ice; ground state degeneracy; electrodeposition